THE NECESSITY OF STRENGTHENING PUBLIC INSTITUTIONS FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Bisina, J. D.; Okolie, U.C. (The Indonesian Journal of Social Studies, 2025)
Anchored on institutional theory and utilizing a qualitative analysis of documentary sources, this study investigates the role of resilient public institutions in advancing sustainable development in Nigeria. Addressing a critical gap in the literature that often prioritizes economic indicators over institutional capacity, the study demonstrates that Nigeria’s persistent development challenges are largely rooted in weak, fragile, and inefficient governance structures. The findings reveal that institutional deficiencies undermine accountability, transparency, and effective policy implementation, thereby reinforcing corruption, poverty, and socio-economic stagnation. Conversely, the study shows that resilient institutions constitute a foundational driver of political stability, effective governance, and inclusive development. By systematically linking institutional resilience to sustainable development outcomes, this study contributes a nuanced institutional perspective to Nigeria’s development discourse. It concludes that sustainable development in Nigeria is unattainable without deliberate and sustained institutional strengthening, positioning institutional reform as a central pathway for unlocking the country’s long-term developmental potential.